Why we need a higher suspicion index of urolithiasis in children. Issue 2 (April 2017) - Marzuillo, Pierluigi; Guarino, Stefano; Apicella, Andrea; La Manna, Angela; Polito, Cesare
Summary: Background: Most children with symptoms of urolithiasis and urinary solute excretion abnormalities leading to stone formation have no calculi revealed by ultrasound or X-ray plain film ("occult urolithiasis"). This covers a large group of children presenting with common symptoms such as abdominal pain, hematuria, and dysuria, often faced by general practitioners and pediatricians. However, half or more of children with urolithiasis could present with abdominal/flank pain without specific urinary symptoms. Study design: We review the current evidence about prevalence, clinical presentation, and radiological detection of overt and "occult" urolithiasis in children, aiming to give readers the instruments to suspect and diagnose urolithiasis while avoiding cost-ineffective and undue diagnostic procedures. Conclusions: It is important to investigate for urolithiasis first by ultrasound and, in specific cases, by urinary metabolic and different imaging studies in the following groups: 1) in children with non-glomerular hematuria or/and dysuria not presenting inflammation of external genitalia; 2) in children with acute/sub-acute or infrequent recurrent abdominal pain and family history of urolithiasis in first or second degree relatives or being at higher risk of developing stones although hematuria and dysuria are lacking; 3) in children under 8 years old, even though pain is central or diffuse to the whole abdomen; and 4) in children presenting risk factors or conditions predisposing to urolithiasis. Finally, it seems reasonable to repeat ultrasound 1–2 years later also in children with "occult" urolithiasis and high risk of developing stones to detect any (re-)appearance of calculi.